Epidemiology of primary brain tumors: current concepts and review of the literature. - Wrensch, Margaret (2002)
The purpose of this review is to provide a sufficiently detailed perspective on epidemiologic studies of primary brain tumors to encourage multidisciplinary etiologic and prognostic studies among surgeons, neuro-oncologists, epidemiologists, and molecular scientists. Molecular tumor markers that predict survival and treatment response are being identified with hope of even greater gains in this area from emerging array technologies. Regarding risk factors, studies of inherited susceptibility and constitutive polymorphisms in genes pertinent to carcinogenesis (for example, DNA repair and detoxification genes and mutagen sensitivity) have revealed provocative findings. Inverse associations of the history of allergies with glioma risk observed in 3 large studies and reports of inverse associations of glioma with common infections suggest a possible role of immune factors in glioma genesis or progression. Studies continue to suggest that brain tumors might result from workplace, dietary, and other personal and residential exposures, but studies of cell phone use and power frequency electromagnetic fields have found little to support a causal connection with brain tumors; caveats remain. The only proven causes of brain tumors (that is, rare hereditary syndromes, therapeutic radiation, and immune suppression giving rise to brain lymphomas) account for a small proportion of cases. Progress in understanding primary brain tumors might result from studies of well-defined histologic and molecular tumor types incorporating assessment of potentially relevant information on subject susceptibility and environmental and noninherited endogenous factors (viruses, radiation, and carcinogenic or protective chemical exposures through diet, workplace, oxidative metabolism, or other sources). Such studies will require the cooperation of researchers from many disciplines.